2016
DOI: 10.1038/ijo.2016.211
|View full text |Cite
|
Sign up to set email alerts
|

Early infant adipose deposition is positively associated with the n-6 to n-3 fatty acid ratio in human milk independent of maternal BMI

Abstract: Background/Objectives Excessive infant weight gain in the first 6-months of life is a powerful predictor of childhood obesity and related health risks. In mice, omega-6 fatty acids (FA) serve as potent ligands driving adipogenesis during early development. The ratio of omega-6 relative to omega-3 (n-6/n-3) FA in human milk (HM) has increased 3-fold over the last 30 years, but the impact of this shift on infant adipose development remains undetermined. This study investigated how maternal obesity and maternal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 53 publications
3
82
0
1
Order By: Relevance
“…Our model also suggested that HM with a higher n-6:n-3 ratio was predictive of faster fat mass gain. This finding replicates a similar finding detected in the larger cohort that did not account for other factors of HM composition (21). Mean HM adiponectin concentrations were inversely correlated with fat mass gain.…”
Section: Discussionsupporting
confidence: 90%
“…Our model also suggested that HM with a higher n-6:n-3 ratio was predictive of faster fat mass gain. This finding replicates a similar finding detected in the larger cohort that did not account for other factors of HM composition (21). Mean HM adiponectin concentrations were inversely correlated with fat mass gain.…”
Section: Discussionsupporting
confidence: 90%
“…With regards to the period of lactation, only few studies have investigated the relation between breast milk PUFA concentrations and the development of adiposity in children who were breastfed. Similar trends were observed, such as a significant increase in body fat mass in 4-months-old breastfed infants whose mother's milk has high ratio of AA/ EPAþDHA (Rudolph et al, 2017), and a negative association between milk DHA content and the fat mass in infants aged from 2 to 7 years (Pedersen et al, 2012). Lastly, few randomized controlled trials have been conducted during pregnancy and/or lactation and exclusively by supplementing the maternal diet with long-chain n-3 PUFA between 0.2 to 1.2 g/d (reviewed in Hauner et al, 2013).…”
Section: Maternal Pufa Intake Obesity and Allergic Diseases 41 Obesitysupporting
confidence: 66%
“…Breast milk from overweight and obese mothers has been reported to have higher levels of insulin and leptin, lower levels of omega-3 PUFA, and higher omega-6:omega-3 PUFA ratios, 153 while showing no differences in macronutrient composition. [154][155][156] Immunological modulators transforming growth factor β2 and sCD-14 have also been reported to be lower in breast milk from obese women.…”
Section: Alterations In Neonatal Nutrition and Infant Microbiomementioning
confidence: 99%